Reformasi Pendidikan Islam di Indonesia Abad Ke-20 dan Abad Ke-21 - Misnatun, Misnatun (IAIN Takengon, 2021)
This article describes the reform of Islamic education in the 20 th century with Islamic thought, as well as ideas that have also entered the world of education. One of the things that can be seen from the view of education is the emergence of efforts to search in materials and methods. Meanwhile, Islamic education reform in the 21st century cannot be separated from the goal of national education, especially in solving problems that occur in the 21st century, which is to build superior people so that they are able to face and solve problems in various lives.